The Influence Of Internal Supervision, Work Discipline And Work Motivation On Employees’ Performance At Satpol Pp And Fire Department,Seluma Regency - Rahma Dania; Siti Hanila; Tri Febrina Melinda (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2024)
Human resources are one of the resources that most determine the success or failure of an organization. In the era of globalization, human resource issues are in the spotlight and the focus for agencies to survive. Where the success of the organization depends on the performance of the organizational actors concerned. An employee is not only required to have knowledge, abilities, and skills but also must have experience, motivation, self-discipline, work enthusiasm, and good work ethic. This research aims to determine the influence of internal supervision, work discipline, and work motivation on the performance of employees of Seluma Regency Satpol PP and Fire Department. This type of research is quantitative descriptive, namely research that uses mathematical models, theories, and/or hypotheses related to natural phenomena. The sample in this study used a purposive sampling technique, where the population sampled at Satpol PP and Fire Department, Seluma Regency were 37 civil servant employees. Based on the results of research conducted it was found that internal supervision, work discipline and work motivation together had a significant effect on employees’ performance at Satpol PP and Fire Department, Seluma Regency with regression multiple linear Y = 8.106 + 0.352 X1+ 0.393 X2 + 0.502